Pengaruh Profitabilitas, Struktur Aktiva, Ukuran Perusahaan dan Peluang Pertumbuhan terhadap Struktur Modal - Natanael Tresno Leonardo; Michael Michael (Jurnal Visi Manajemen, 2024)
The covid-19 pandemic has had a major impact on the economic and health sectors in indonesia. The health and technology sectors have experienced significant growth due to changes in economic behavior resulting in increased public demand for health and technology products. However, the challenge that arises is the financial resilience of companies in both sectors amid significant economic growth. This can be seen from capital structure policy of companies in both sectors. This study aims to analyze the effect of profitability, asset structure, company size, and growth opportunities on capital structure in health and technology companies listed on the IDX for the 2019-2022 period by taking into account the completeness and suitability of the data during that period. This study used purposive sampling technique to obtain 21 companies as research samples. This research was conducted using a quantitative method with a data panel data regression approach by adopting the Fixed Effect Model as the best model and processed using the Eviews 13 application. The results of the analysis show that profitability has a negative effect on capital structure, while company size and growth opportunities have a positive effect on capital structure, while asset structure has no effect on capital structure.